Whole-Genome Sequence of High Salt and Heavy Metal-Tolerant Bacillus stratosphericus Strain 5Co, Isolated from Lichen Usnea florida in Central Florida, United States - Lata, Pushpa (Genome Announc, 2017)
Bacillus stratosphericus strain 5Co was isolated from lichen Usnea florida in central Florida, United States. Here, we report a draft genome sequence of this strain, which consists of 159 contigs spanning 3,628,496 bp, with a G+C content of 41.3% and comprises 3,729 predicted coding sequences.